The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s10692-005-0010-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the thermal properties of aromatic fibres (polyoxazole, polyimide, and polyaramid)

Abstract: The thermal properties of the aromatic fibres Arselon, Arselon-C, Arimid, and Armos, as-spun and heattreated are investigated using methods of thermomechanical and dynamic thermogravimetric analysis and differential scanning calorimetry. According to the TMA data, Arselon, Arselon-C, Arimid, and heat-treated Armos fibres retain size stability up to 400°C. Shrinkage is no more than 1-2%. As-spun Armos fibres lengthen insignificantly (under 7%). The temperature characteristics of aromatic fibres obtained by TGA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…For a detailed evaluation of the thermal characteristics of POD fibres, they were investigated by methods of thermomechanical analysis (TMA), dynamic thermogravimetry (TGA), differential scanning calorimetry (DSC), and differential thermal analysis (DTA) in air and in nitrogen medium [14][15][16], and preservation of their mechanical properties was investigated in a wide temperature range. The results of our studies corresponding to the data in [1,4,6,7] and are examined in detail below.…”
Section: Thermal Properties Of Polyoxazole Fibres and Filamentsmentioning
confidence: 97%
“…For a detailed evaluation of the thermal characteristics of POD fibres, they were investigated by methods of thermomechanical analysis (TMA), dynamic thermogravimetry (TGA), differential scanning calorimetry (DSC), and differential thermal analysis (DTA) in air and in nitrogen medium [14][15][16], and preservation of their mechanical properties was investigated in a wide temperature range. The results of our studies corresponding to the data in [1,4,6,7] and are examined in detail below.…”
Section: Thermal Properties Of Polyoxazole Fibres and Filamentsmentioning
confidence: 97%
“…Much work [13,14,15,16] has been performed to investigate the thermal stability of these fibers for use in high-temperature environments and fire applications. These materials are chemically similar to other fibers used in fire-resistant applications, such as para and meta-aramid fibers, so interest in their thermal properties is not surprising.…”
Section: Moisture Sorption and Other Propertiesmentioning
confidence: 99%
“…These materials are chemically similar to other fibers used in fire-resistant applications, such as para and meta-aramid fibers, so interest in their thermal properties is not surprising. The decomposition tempera-Study of Acid Generation from Copolymer Fibers based on 5-amino-2-(p-aminophenyl)-benzimidazole tures in air for Armos showed that it was stable to oxidation and onset of degradation to approximately 400 • C [15]. A separate study on the thermal stability of PPTA, SVM, Rusar, and Armos fibers in which the fibers were exposed to 250 • C for periods of time between 0 h and 100 h showed that the mechanical properties of the SVM fibers decreased the most rapidly, and that there was little difference in the thermal stability of the other fibers examined [13].…”
Section: Moisture Sorption and Other Propertiesmentioning
confidence: 99%
“…Due to the above, comparative studies of the thermooxidative degradation and size stability (lengthening or shrinkage) of the fibres and thread listed above were conducted to evaluate their behavior in conditions close to the conditions of use and to refine some previously obtained data [16,17].…”
Section: And E a Pakshvermentioning
confidence: 99%